Interjections in the speech of British royal family members - Natalya V. Panina; Oksana O. Amerkhanova (Peoples' Friendship University of Russia (RUDN University), 2018)
The article draws on publicly available interviews to consider the range and functions of interjections used by members of the British royal family as elements of speech behaviour elucidating the corresponding features of their speech portraits in the framework of the lingua-pragmatic and socio-cultural lines of research supported by qualitative and quantitative methods of data analysis. The authors make inferences concerning the inevitable affinity of interjections, contemplate their role in the natural process of speech formation, highlight the reasons for the lack of conative and phatic interjections as well as the scarcity of emotive interjections and the frequency of their occurrence in the respondents' speech. The results obtained support the arguments of the anthropocentric approach in linguistic studies, proclaiming that emotion, an inseparable part of human activity, can be verbally expressed in the form of interjections.